2017
DOI: 10.4081/ecj.2017.6600
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory testing in the emergency department: An Italian Society of Clinical Biochemistry and Clinical Molecular Biology (SIBioC) and Academy of Emergency Medicine and Care (AcEMC) consensus report

Abstract: The mainstay of patient-oriented laboratory testing in emergency settings entails selecting number and type of tests according to valid criteria of appropriateness.Since the pattern of urgent tests requesting is variable across different institutions, we designed a joined survey between the Academy of Emergency Medicine and Care (AcEMC) and the Italian Society of Clinical Biochemistry and Clinical Molecular Biology (SIBioC) for reaching tentative consensus about the most informative diagnostic tests in emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…1,2 Since rapid and accurate diagnoses followed by appropriate treatments are the mainstays in the field of Emergency Medicine (EM), the Laboratory Medicine (LM) shall modulate its actual organization to fulfill these tasks and hence provide rapid and accurate tests that may allow Emergency Physicians (EPs) to make early rule out or rule in of most urgent and acute disorders. 3 Two Italian scientific societies of EM (Academy of Emergency Medicine and Care, AcEMC) and LM (Italian Society of Clinical Biochemistry and Clinical Molecular Biology, SIBioC) have been precursor for establishing a fruitful collaboration, with publication of many consensus documents on important topics such as panels of urgent diagnostic tests, 4,5 diagnosing acute coronary syndrome, 6 sepsis, 7 and venous thromboembolism. 8 It is commonly perceived that a main obstacle for an effective partnership between EM and LM is the lack of sufficient reciprocal knowledge and understanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Since rapid and accurate diagnoses followed by appropriate treatments are the mainstays in the field of Emergency Medicine (EM), the Laboratory Medicine (LM) shall modulate its actual organization to fulfill these tasks and hence provide rapid and accurate tests that may allow Emergency Physicians (EPs) to make early rule out or rule in of most urgent and acute disorders. 3 Two Italian scientific societies of EM (Academy of Emergency Medicine and Care, AcEMC) and LM (Italian Society of Clinical Biochemistry and Clinical Molecular Biology, SIBioC) have been precursor for establishing a fruitful collaboration, with publication of many consensus documents on important topics such as panels of urgent diagnostic tests, 4,5 diagnosing acute coronary syndrome, 6 sepsis, 7 and venous thromboembolism. 8 It is commonly perceived that a main obstacle for an effective partnership between EM and LM is the lack of sufficient reciprocal knowledge and understanding.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the authors of this article also concluded that Spanish hospitals would have saved >1 million unnecessary tests by simply harmonizing the diagnostic approaches and establishing a favorable interdepartmental cooperation between EPs and laboratory professionals. 13 Despite some reliable guidance on appropriateness of laboratory test requests in the ED has been published by SIBioC, 14 then mutually agreed by both SIBioC and AcEMC, 4 the real scenario of attitudes and beliefs of EPs on lab tests utilization in clinical practice remains largely unclear. Therefore, this original study was designed to explore this field of medical knowledge, by using a survey on attitudes and beliefs in laboratory diagnostics which was disseminated among many Italian EPs.…”
Section: Introductionmentioning
confidence: 99%